Youth, Media and the Asian Family: Contextualising our Understanding, Understanding our Context - Lim, Sun Sun (2014)
13th Asian Media Information & Communication Centre Annual Conference on ICT & Media Inputs & Development Outcomes - Impact of New & Old Media on Development in Asia, Bangkok, Thailand, July 2004